2016
DOI: 10.1002/cncy.21735
|View full text |Cite
|
Sign up to set email alerts
|

Morphologists overestimate the nuclear‐to‐cytoplasmic ratio

Abstract: BACKGROUND:The Paris System for Reporting Urinary Cytology (TPS) has defined nuclear-to-cytoplasmic (N:C) ratio cutoff values for several of its risk-stratified diagnostic categories. However, because pathologists are not trained to recognize strict N:C ratio cutoff values, a previously designed survey was used to determine whether pathologists could accurately identify N:C ratios according to TPS standards. METHODS: Participants were instructed to estimate the N:C ratio of ideal (line drawing) and real (cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
63
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 7 publications
2
63
1
Order By: Relevance
“…Additionally, cells with elevated N/C ratios can be seen in a variety of conditions including instrumented urine as well as reactive and degenerative changes. Other studies have also suggested poor interrater reliability [9,11] , consistent with our results. The identification of a high N/C ratio along with other features resulted in a higher specificity and was more predictive of malignancy.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Additionally, cells with elevated N/C ratios can be seen in a variety of conditions including instrumented urine as well as reactive and degenerative changes. Other studies have also suggested poor interrater reliability [9,11] , consistent with our results. The identification of a high N/C ratio along with other features resulted in a higher specificity and was more predictive of malignancy.…”
Section: Discussionsupporting
confidence: 83%
“…A collection of images was provided to each reviewer detailing the morphological features in question. We utilized photos from TPS [8] and Zhang et al [9] .…”
Section: Methodsmentioning
confidence: 99%
“…The nuclear/cytoplasmic (N/C) ratio has been utilized for the diagnosis of carcinoma [1][2][3][4][5][6][7][8] and the grading of carcinomas. [16][17][18] Vaickus and Tambouret 19 demonstrated that trained morphologists were reasonably accurate at estimating N/C ratio, but Zhang et al 20 using similar methods and definitions showed that morphologists overestimated nuclear-to-cytoplasmic ratio. Recently, The Paris System for Reporting Urinary Cytology utilized N/C ratios as important criteria for defining the categories: atypical urothelial cells (AUC), suspicious for high grade urothelial carcinoma (suspicious), and high grade urothelial carcinoma (HGUC).…”
mentioning
confidence: 99%
“…18,19 The large number of specimens included in our study to allow for the required statistical power precluded glass slide review of every specimen. Several studies have shown that pathologists have difficulty determining an accurate nuclear-to-cytoplasmic ratio when analyzing individual cells; accurate assessment in UTF in which cytoplasmic borders are often indistinct may not be possible.…”
Section: Discussionmentioning
confidence: 99%